2007
DOI: 10.1017/s0007485307005093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kaolin particle film on Myzus persicae (Hemiptera: Aphididae) behaviour and performance

Abstract: The emergence of resistance mechanisms to, and revocation of, many insecticides used in the control of the polyphagus aphid pest, Myzus persicae (Sulzer), has increased the pressure to develop novel approaches for the control of the pest in many crops. Kaolin-based particle films provide a physical barrier against insect pests and show considerable potential for controlling M. persicae. We conducted a series of laboratory experiments to investigate the mode of action of kaolin against aphids. The material appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
6
0
3
Order By: Relevance
“…Repellency of kaolin particle film to various insects has been reported in the literature. Barker et al 32 found that, when Myzus persicae (Sulzer) were given a choice between kaolin‐particle‐film‐treated and untreated (or water‐solvent‐treated) leaf areas, both adults and nymphs exhibited a significant preference for non‐kaolin‐particle‐film‐treated host plants. Rejection of kaolin‐particle‐film‐treated plant material occurred very rapidly (<20 min).…”
Section: Discussionmentioning
confidence: 99%
“…Repellency of kaolin particle film to various insects has been reported in the literature. Barker et al 32 found that, when Myzus persicae (Sulzer) were given a choice between kaolin‐particle‐film‐treated and untreated (or water‐solvent‐treated) leaf areas, both adults and nymphs exhibited a significant preference for non‐kaolin‐particle‐film‐treated host plants. Rejection of kaolin‐particle‐film‐treated plant material occurred very rapidly (<20 min).…”
Section: Discussionmentioning
confidence: 99%
“…Kaolien mineraal kan worden toegepast als poeder dat op het blad een dunne witte laag achterlaat en dat bladluizen door de sterk reflecterende werking kan afweren (Barker et al 2007)…”
Section: Kaolienunclassified
“…Kaolin has been reported by Ma and Wang (2006) to be used in treatment of oil polluted water with about 99 % removal of chemical oxygen demand, biological oxygen demand, total dissolve solids and hardness. Other areas where it is utilized are pharmaceutical industry, for production of drug used in treatment of various gastrointestinal problems; cosmetics for production of talc; production of glossy paper for magazine and newspaper; paints production for gloss level control, and insecticides to control arthropods (Barker et al, 2007;Belloto et al, 1995). The active chemical component responsible for wastewater treatment in kaolin is aluminium silicate hydroxide (Al 2 Si 2 O 5 (OH) 4 ) popularly called kaolinite.…”
Section: Introductionmentioning
confidence: 99%